GOD'S PRESENCE AMID WOMEN'S MARGINALIZATION AND SUFFERING: A CONTEXTUAL THEOLOGICAL PERSPECTIVE ON GENDER AND GOD'S JUSTICE - Gomgom Simorangkir; Riris Johanna Siagian (RADJA PUBLIKA, 2025)
This study highlights God's presence amidst the marginalization and suffering of women, particularly in the context of Batak culture, which remains steeped in patriarchal values. Using a qualitative approach and a contextual theology paradigm, this study reinterprets women's experiences as a locus theologicus to understand God's justice and provision. Women's marginalization is evident in various social, customary, and ecclesiastical aspects, where women are often positioned as